Crop Production 2020 – Corn, Sorghum, Soybean, and Sunflower Variety Testing - G. F. Sassenrath; L. Mengarelli; J. Lingenfelser; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2021)
This is a summary of the variety testing for corn, sorghum, soybean, and sunflower. Nine corn varieties were tested in 2020, with an average yield of 107.6 bu/a. Twenty-four cultivars of soybeans from maturity groups (MG) 3-4 and twenty-seven cultivars from MG4-5 were tested in both full-season and double-cropped management. Full-season beans yielded an average of 54.5 bu/a for MG3-4 and 58.8 bu/a for MG4-5, which was greater than the average yields in the double-cropped beans at 32 bu/a for MG3-4 and 40.5 bu/a for MG4-5. The state-wide average soybean yield in 2020 was higher than the 10-year average. Nine cultivars of oilseed sunflowers yielded 1307 lb/a across all cultivars, slightly below the 10-year state average yield.
Keywords: crop variety testing; soybeans; full season; double cropped; corn; sunflower; sorghum